2022
DOI: 10.1002/ijgo.14190
|View full text |Cite
|
Sign up to set email alerts
|

OPEC study: An international multicenter study of ovarian preservation in endometrial cancers

Abstract: Objective To evaluate the feasibility and oncological safety of ovarian preservation in early stage endometrial adenocarcinoma (EC) patients aged 40 and below. Methods A total of 11 institutions from eight countries participated in the study. 169 of 5898 patients aged ≤40 years were eligible for the study. Patients with EC treated between March 2007 and January 2019 were retrospectively assessed. Results The median duration of follow‐up after EC diagnosis was 59 months (4–187). Among 169 participants, ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…No difference in recurrence-free and OS was observed between the two groups. The authors concluded that ovarian preservation appears to be well tolerated without having any adverse impact on survival in women aged 40 years or less with FIGO-stage I endometrial cancer [20]. Interestingly, a recent case report described the ovarian recurrence 12 months after primary treatment of a postmenopausal woman with FIGO-stage IA grade 1 endometrioid endometrial adenocarcinoma [21].…”
Section: Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…No difference in recurrence-free and OS was observed between the two groups. The authors concluded that ovarian preservation appears to be well tolerated without having any adverse impact on survival in women aged 40 years or less with FIGO-stage I endometrial cancer [20]. Interestingly, a recent case report described the ovarian recurrence 12 months after primary treatment of a postmenopausal woman with FIGO-stage IA grade 1 endometrioid endometrial adenocarcinoma [21].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Two retrospective studies specifically looked at the oncological safety of ovarian preservation in early-stage endometrial adenocarcinoma [19 ▪ ,20]. Nasioudis et al [19 ▪ ] analyzed 2941 patients aged 45 years or less diagnosed between January 2004 and December 2015 with FIGO-stage I grade 2 or 3 endometrioid endometrial carcinoma, who underwent hysterectomy with or without bilateral salpingo-oophorectomy from the National Cancer Database [19 ▪ ].…”
Section: Endometrial Cancermentioning
confidence: 99%